2021
DOI: 10.1016/j.seppur.2020.117998
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic polycarbosilane membranes for purification of solar hydrogen

Abstract: Superhydrophobic membranes composed of an organic-inorganic hybrid polymer, namely polycarbosilane (PCS) with Mw of 4-8.9 ×10 3 , were formed on a mesoporous γ-Al 2O3-modified α-Al2O3 porous support. Under dry condition at 50 • C, the supported PCS membranes exhibited H2 permeance of 1.1-1.6 ×10 −6 mol⋅m −2 ⋅s −1 ⋅Pa −1 and H2/N2 selectivity of 9.7-12.6 together with unique H2/He selectivity of 1.4-1.6. Even under saturated humidity at 50 • C, H2 permeance remained at 7.7 ×10 −8 mol −1 m −2 s −1 Pa −1 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…H 2 /N 2 selectivity [188]. On the contrary, corrosion protection requires sufficiently thick HMDSO-based plasma coatings to block water penetration within relevant time scales.…”
Section: Deposition Of Polymer-like Soft Plasma Coatingsmentioning
confidence: 99%
“…H 2 /N 2 selectivity [188]. On the contrary, corrosion protection requires sufficiently thick HMDSO-based plasma coatings to block water penetration within relevant time scales.…”
Section: Deposition Of Polymer-like Soft Plasma Coatingsmentioning
confidence: 99%
“…A comparison of the AHPCS-derived membranes with previously reported membranes, including PCS-derived SiC, 15 organosilica, 7,8,31,32 metal-doped SiO 2 , 33 and zeolites, 34–41 is summarized in Fig. 12.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Iwamoto et al reported polycarbosilane (PCS)-derived membranes, which showed H 2 permeance of 7.7 Â 10 À8 mol m À2 s À1 Pa À1 with H 2 /N 2 selectivity of 26 under saturated humidity at 50 1C. 15 Wang et al 16 fabricated PCS-derived membranes and reported H 2 permeance of 1-2 Â 10 À6 mol m À2 s À1 Pa À1 at 500 1C with H 2 /N 2 selectivity of 31. However, their performance under hydrothermal treatment has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%